2011
DOI: 10.1021/ma2014639
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Complex Micelles in Amphiphilic Mixtures: A Coarse-Grained Mean-Field Study

Abstract: Binary mixtures of amphiphiles in solution can self-assemble into a wide range of structures when the two species individually form aggregates of different curvatures. In this paper, we focus on small, spherically-symmetric aggregates in a solution of sphere-forming amphiphile mixed with a smaller amount of lamella-forming amphiphile. Using a coarsegrained mean-field model (self-consistent field theory, or SCFT), we scan the parameter space of this system and find a range of morphologies as the interaction str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…It well satises the widely accepted rule that with the increase of the hydrophilic volume fraction, the aggregations change from lamellar structures to micelles. 9,10 The detailed morphologies and the mechanism of the morphological changing from the compound vesicles to network micelles will be discussed in the following. Table 1 The interaction parameters of bead-bead pairs, a ij (k B T/r c ) During the self-assembly, the randomly mixed amphiphiles rst aggregate to small disk-like micelles driven by their hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It well satises the widely accepted rule that with the increase of the hydrophilic volume fraction, the aggregations change from lamellar structures to micelles. 9,10 The detailed morphologies and the mechanism of the morphological changing from the compound vesicles to network micelles will be discussed in the following. Table 1 The interaction parameters of bead-bead pairs, a ij (k B T/r c ) During the self-assembly, the randomly mixed amphiphiles rst aggregate to small disk-like micelles driven by their hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to regulate the self-assembled nanostructures and predict their specic functions from the building molecules. Previous studies [7][8][9][10] found that the self-assembled structures of amphiphiles are denitively determined by their architectures, such as the size of the hydrophilic and hydrophobic components. Generally, if the hydrophilic part is larger than the hydrophobic part, the micelles form.…”
Section: Introductionmentioning
confidence: 99%
“…In eqn (1) and ( 2), V HT (r) is the (effective) repulsive interaction between heads and tails of distinct molecules. V conn (r) in eqn (5) for the propagator G(r,r 0 ) is the connectivity potential between heads and tails within a single molecule. These two potentials will in general be chosen to reflect properties of the amphiphilic molecules.…”
Section: Theorymentioning
confidence: 99%
“…Other dynamic [6,7,9,35,36] or lower dimensional SCFT studies [5,8,9,37] have also pointed towards a universality of behaviour between lipids and amphiphilic block copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation